A risk-based approach to measuring population micronutrient status from blood biomarker concentrations - Ghosh, Santu; Kurpad, Anura V.; Sachdev, Harshpal S.; Thomas, Tinku (Frontiers in Nutrition, 2022)
Background Nutrient biomarkers and their definitive cut-offs are used to classify individuals as nutrient-deficient or sufficient. This determinism does not consider any uncertainty, and a probability approach, using biomarker distributions, is then preferable to define the risk of nutrition deficiency when in populations. Method Healthy 1–19-year-old children and adolescents were selected from the Comprehensive National Nutrition Survey (CNNS), to obtain probability distributions of their retinol, zinc and vitamin B12, along with erythrocyte folate. Model-based estimates of location, scale and shape parameters of these distributions were obtained across ages. Subsequently, in the entire sample of 1-19 year old children of CNNS, the population risk of deficiency (PRD) which is average risk of deficiency in individuals in the population was computed, which is ‘of concern’ when >50%. When individual risk of deficiency is >97.5% it is called ‘severe risk of deficiency’ (SRD). Results In the entire CNNS sample, the PRD of concern was low for serum retinol (3.6 to 8.2%), zinc (0 to 5.5%), vitamin B12 (2.3 to 7.2%) and erythrocyte folate (4.2 to 9.7%) across age and sex groups. Conclusion This proposed method assesses the adequacy of nutrient exposures without relying on pre-defined deterministic biomarker cut-offs to define micronutrient deficiency and avoids errors in exposure assessment.